Communicating Preferences to Improve Recommendations - Amir Habibi (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
I study a cheap talk model between a buyer and a seller with two goods for sale. There is two-sided (independent) private information with sequential, two-way communication. In the first stage, the buyer communicates her private preferences to the seller. In the second stage, the seller communicates the quality of the goods to the buyer. When the buyer's preference is about which attribute common to both goods she prefers, the seller strictly benefits from the buyer communicating her preferences. Whereas when the buyer's preference is about which good she prefers, this is never the case.
Keywords: D82; L15; 330; cheap talk; strategic communication; product recommendations